Integrasi Ilmu Keislaman di Era Kontemporer: Kritik atas Dikotomi Ilmu Agama dan Ilmu Umum - Khoridatul Ilmiyah; Nursyam .; Mufida Cholil; Nur Wahidah (UAS PRESS, 2026)
The dichotomous paradigm has long influenced Islamic education systems, resulting in fragmented knowledge and limited interdisciplinary engagement. This study employs a qualitative library research method, analyzing classical and contemporary Islamic scholarly works as well as reputable academic journals related to epistemology, Islamic education, and knowledge integration. The findings indicate that the dichotomy of knowledge is not rooted in Islamic epistemology but rather emerged from historical, colonial, and modern educational influences. Islamic intellectual tradition fundamentally recognizes the unity of knowledge (tawhid al-‘ilm), where revelation, reason, and empirical inquiry are interconnected. The study argues that integrating Islamic sciences requires an epistemological reconstruction that transcends the separation between sacred and profane knowledge. Such integration has significant implications for curriculum development, research orientation, and the strengthening of Islamic higher education institutions in addressing contemporary challenges. This article recommends the development of integrative curricula and interdisciplinary research models grounded in Islamic worldview to overcome knowledge fragmentation.